Effect of Nitriding Temperature and Nitriding Time On Magnesium, MgAZ91D Alloy - TG. ALI, TENGKU MOHAMAD AMIRUL (IRC, 2018)
Magnesium and its alloy are widely known such as MgAZ91D are receiving more consideration especially in telecommunication industries, instrumental industry, electrical industry and automotive industry due to its excellent properties such as low density, high specific strength and high recyclability. However, it possesses a low surface hardness which can weaken the adhesion properties especially when hard coating is applied. The need of hard coating is important to enhance its corrosion resistance because its corrosion resistance is low compare to other metals. In this project paper, nitriding process is carried out to modify the surface properties of MgAZ91D in enhancing its corrosion resistance. The nitriding process involved in this project is gas nitrding process with a specific end goal to identify the impact of the magnesium alloy on surface hardness, case depth and surface roughness by using pure nitrogen gas that can form a nitride layer to increase the surface hardness of the material. Different quality of nitride layer will be formed based on different setup of temperature and time used in this project. Five nitriding temperatures were set which were at 300 ̊C, 350 ̊C, 400 ̊C, 450 ̊C and 500 ̊C, for a nitriding period of 1 hour and 2 hours respectively. The specimens are to be magnified by metallographic test before and after nitride process like Optical Microscope (OM) for basic microstructure of MgAZ91D alloy. Mechanical tests are used to test and analysed the surface hardness and case depth of the nitride MgAZ91D using micro hardness testing machine such as Vickers Hardness test, Scratch test and Surface Roughness test to obtain the result of the performance of the nitride layer. The best setting of the nitriding process is concluded. The hardness of untreated material and nitride specimens are analysed. The best specimen is chosen which determines the life of the material and it improves the surface hardness, surface roughness and case depth for corrosion applications.